Enhancing Balance, Strength, Flexibility and Spatiotemporal Gait Parameters in Pediatric Cerebral Palsy: Treadmill Training at Variable Inclinations - Neşe Toktaş; Hande Şenol; Mustafa Hapak; Ahmet Alptekin; Berna Ramanlı (Pamukkale Spor Bilimleri Dergisi)
This study aimed to evaluate the effect of treadmill training at different inclinations on balance, strength, flexibility, and gait parameters in children with cerebral palsy in addition to traditional physiotherapy applications. Forty-two participants with cerebral palsy aged 7–18 years and at Gross Motor Function Classification System level II were randomized into three groups: downhill walking, uphill walking, and walking with no incline. Balance, isometric strength, flexibility, and gait parameters were assessed at baseline (2nd week) and at 11th week. The groups were provided with treadmill training and conventional treatment. All groups showed improvement in balance. Isometric strength values showed improvement in knee flexion on the affected side for both downhill walking and uphill walking groups, as well as in knee extension force for the uphill walking and walking with no incline groups. In flexibility, hip flexion, hip extension, and ankle dorsiflexion improved in all groups, while knee flexion and ankle plantar flexion improved only in downhill walking and walking with no incline. The duration of the modified timed up-and-go test showed significant improvements in both the downhill walking and uphill walking groups. Treadmill training performed at different inclinations improved balance, isometric strength, flexibility, and gait parameters on both the affected and less affected sides.